A new fractional integral associated with the Caputo-Fabrizio fractional derivative - Moumen Bekkouche, M.; Guebbai, H.; Kurulay, M.; Benmahmoud, S. (SPRINGER-VERLAG ITALIA SRL, 2021)
In this article, we introduce a new fractional integral (FI) associated with the Caputo-Fabrizio fractional derivative. As a theoretical example, we have solved a fractional boundary value problem (BVP) using the proposed FI. A Matlab script to solve this BVP is also provided.
Keywords: Caputo-Fabrizio fractional derivative; Fractional integral; Fractional boundary value problem; Green's function; Mathematics